Digital transformation of the healthcare sector as a factor in improving the quality of medical services (using the example of the East Kazakhstan region) - Abdrakhmanova, Zh.S.; Nurekenova, E.S.; Karipova A.Т.; Kosarev, N.A. (BUKETOV BUSINESS REVIEW, 2023)
Object: The purpose of this study is to examine the variables influencing the growth of healthcare digitalization in the East Kazakhstan region using the correlation and regression analysis method. Methods: The traditional methods of economic (comparison, detailing) and econometric analysis (correlationregression analysis) were used in the work. As a performance measure, the number of organizations in the East Kazakhstan area that employ experts in information and communication technology in the field of healthcare is used. Findings: The results obtained during the study made it possible to identify weaknesses in the functioning and regulation of the healthcare sector in the East Kazakhstan region, to assess the quality of medical services provided and to identify promising areas in the implementation of digital technologies in the healthcare system. The need to modernize digital healthcare, its state regulation and support is shown. Conclusions: According to the report, the degree of information and communication technology adoption in the health care system has an impact on both the growth of the medical industry and the standard of services offered. Digital technologies make it possible to improve the relationships, guarantee comfortable access to medical services and recreate two-way ties for a long period of time. Also, digital technologies help to develop “smart health” methods to improve quality and reduce costs, support the efforts of the healthcare system to move to new models of patientcentered care. But on the path of striving to facilitate the work of healthcare and the relationship with the patient, one should not forget about the possible risks of leakage of personal data, cyber attacks, etc. In this regard, the development of this direction will require high costs and investments.